2021
DOI: 10.1108/ijhg-02-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Participation of nongovernmental organizations in Iran's health-care system: challenges and suggestions for improvement

Abstract: PurposeNongovernmental organizations (NGOs) play a critical role in modern health-care systems complementing state organizations. The purpose of this paper is to investigate the challenges of NGOs' participation in Iran's health-care system.Design/methodology/approachThis qualitative study was conducted in 2020. Data were collected through semi-structured interviews with 26 participants: 11 managers and experts at the office of NGOs in the Ministry of Health (MOH) and universities of medical sciences and 15 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Moreover, nonprofits’ performance depends on their capacity, and their failure to do so results in challenges and impediments (Ebrahimi et al 2021 ). Some studies have found that building capacity incurs costs and increases cost operation, affecting the efficiency of funds spent on beneficiaries (Battilana et al 2013 ; Cheah et al 2019b ).…”
Section: Discussion and The Directions Of Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nonprofits’ performance depends on their capacity, and their failure to do so results in challenges and impediments (Ebrahimi et al 2021 ). Some studies have found that building capacity incurs costs and increases cost operation, affecting the efficiency of funds spent on beneficiaries (Battilana et al 2013 ; Cheah et al 2019b ).…”
Section: Discussion and The Directions Of Future Researchmentioning
confidence: 99%
“…A growth in management capacity expenses (salaries, professional fees, marketing, and system) mediates a positive relationship between the overhead ratio and the success of nonprofits. However, capacity in management is staff, financial, and project management (Ebrahimi et al 2021 ), which are interchangeable. Thus, management capacity is the management’s ability and capability to plan, manage, and implement resources and activities to achieve the social mission.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…NGO registration system, interaction with other NGOs, private sectors and government, and internationalization and financial crisis are the most challenging issues facing the NGOs. Despite these challenges, the NGOs helped Iran to cope with COVID-19 [ 23 ].…”
Section: Ngos In Iran and Their Role In Coping With Covid-19mentioning
confidence: 99%
“…Two of the articles (Jain and Dhir, 2021;Mittal et al, 2021) describe healthcare issues in India. Four further articles address current issues in the Association of Southeast Asian Nations (ASEAN) area (Ashraf and Ong, 2021;Baithesda et al, 2021;Del Rosario et al, 2021;Sooampon et al, 2021), whilst the two outliers address healthcare in Iran (Ebrahini et al, 2021) and Norway (Aase et al, 2021). Two articles focus on the role of non-government organisations (NGOs) in healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles focus on the role of non-government organisations (NGOs) in healthcare. The relationship between these is that they both address the issue of NGOs in developing countries (Ebrahini et al, 2021;Jain and Dhir, 2021). A further two articles focus on improving care for elderly patients (Baithseda et al, 2021;Aase et al, 2021).…”
Section: Introductionmentioning
confidence: 99%